1988
DOI: 10.1016/0895-4356(88)90094-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective studies in scleroderma: Effect of potassium para-aminobenzoate on survival

Abstract: Demographic and survival data are presented for 390 patients with scleroderma. For the entire group an estimated 81.4% survived 5 years from diagnosis and 69.4% survived 10 years. Life-table analyses revealed that adequate treatment with potassium para-aminobenzoate (Potaba KPAB) was associated with improved survival (p less than 0.01); 88.5% 5 year survival rate and 76.6% 10 year survival rate for adequately treated patients. Five and ten year survival rates for patients never treated with KPAB were 69.8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Previous univariate survival analysis studies indicated that the presence of diffuse skin involvement,19 male sex,4 6 8 11 older age at the onset of the SSc,13 5 – 7 1214 internal organ manifestations including the heart,17 1013 1517 kidney,2 – 4 6 7 1315 17 18 gastrointestinal tract,2 15 18 lung involvements,17 10 11 14 15 18 pericarditis,3 4 14 clinical signs of right heart failure,7 11 pigmentation disturbances,2 nailfold capillary loss seen on capillaroscopy,14 joint contractures,10 and decreased oral aperture1 were associated with poor survival. Anti-topoisomerase antibody,1 5 7 anaemia,13 13 14 18 increased erythrocyte sedimentation rate (ESR),13 5 10 13 increased C-reactive protein (CRP) level,4 abnormal urine sediment,1 16 proteinuria without scleroderma renal crisis1 13 were also associated with a bad prognosis of the disease, while anti-centromore (ACA) positivity6 was a favourable prognostic factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous univariate survival analysis studies indicated that the presence of diffuse skin involvement,19 male sex,4 6 8 11 older age at the onset of the SSc,13 5 – 7 1214 internal organ manifestations including the heart,17 1013 1517 kidney,2 – 4 6 7 1315 17 18 gastrointestinal tract,2 15 18 lung involvements,17 10 11 14 15 18 pericarditis,3 4 14 clinical signs of right heart failure,7 11 pigmentation disturbances,2 nailfold capillary loss seen on capillaroscopy,14 joint contractures,10 and decreased oral aperture1 were associated with poor survival. Anti-topoisomerase antibody,1 5 7 anaemia,13 13 14 18 increased erythrocyte sedimentation rate (ESR),13 5 10 13 increased C-reactive protein (CRP) level,4 abnormal urine sediment,1 16 proteinuria without scleroderma renal crisis1 13 were also associated with a bad prognosis of the disease, while anti-centromore (ACA) positivity6 was a favourable prognostic factor.…”
mentioning
confidence: 99%
“…The Cox proportional-hazards model showed that older age,3 6 11 12 14 19 renal involvement,3 6 14 19 severe lung involvement,2 5 13 18 clinical signs of right heart failure,7 11 the presence of diffuse SSc,3 6 and a greater extent of skin involvement2 were unfavourable independent prognostic signs.…”
mentioning
confidence: 99%
“…Several studies have evaluated extent of skin and organ involvement, nail bed capillary involvement, autoantibodies, and signs of inflammation or immune activation for prognostic significance. In univariate analysis, numerous poor prognostic factors have been reported including diffuse skin involvement [3][4][5][6][7][8][9][10][11][12][13], male sex [3,8,10,14], older age at the onset of the SSc [3][4][5][6][7]9,13,[15][16][17], internal organ involvement including the heart [3-9,12, [14][15][16][18][19][20], kidney [3,4,6-8, 13,[16][17][18]20,21], gastrointestinal tract [6, 18,21], lung [3-9, 14,17,18,21,22], presence of pericardial effusion or pericarditis [7,8,17], clinical signs of right heart failure [9,14], antitopoisomerase antibody positivity [4,…”
Section: Survivalmentioning
confidence: 99%
“…[43]. In base of this last study based on 17 studies, we could state that mortality is over 2.7-fold compared to the general population ( Table 4 and Figure 2) [5,17,24,26,29,30,31,33,37,40,42,[48][49][50][51][52][53]. Mortality has been decreasing over time and notoriously after 1990, being more reasonable to accept nowadays an SMR over 2.4-fold in a patient diagnosed today ( Figure 2).…”
Section: Mortalitymentioning
confidence: 99%